Teaching society? - Miskolczi, Péter (Družboslovne razprave, 2016)
Sociology's possible roles of producing knowledge and shaping society can suggest several different approaches to teaching. In our article, we conduct a macro-level review of sociology's role in society. We touch upon the issue of value-free sociology (stressing scientific neutrality) and then refer to Burawoy's programme of public sociology (advocating involvement in civil society) and its criticism. We connect this with the Hungarian experience which shows that while sociology was historically involved, to various extents, in shaping society by either legitimating or challenging the status quo, nowadays this function seems to be superfluous for the architects of political power. In such a social context, even the goals of improving students' reflexivity and critical thinking might be seen as a political act.
Keywords: Sociologija; Sociology; Družbena vloga; Social role; Study and teaching; Učenje in poučevanje; Madžarska; Hungary; učeča se družba; kritično mišljenje